DESAIN DAN PENGEMBANGAN SECURE INTEGRATION MODEL PADA INTEGRASI LAYANAN MELALUI MINI PROGRAM: STUDI KASUS MOBILE BANKING PT XYZ - Khols, Ghiant Masua; Setiadi Yazid (AI Society & STMIK Indonesia, 2025)
This research develops a Secure Integration Model based on OAuth 2.0, AES-256 encryption, and Unique Code tokenization to provide a secure integration between PT XYZ's mobile banking and its partners through the Mini Program. The primary objective of this study is to enable seamless login and customer order payments using virtual accounts with a high level of security. The model is designed to ensure that only authorized entities can access sensitive data through robust authentication and authorization mechanisms. The development of this model serves as an essential solution to provide a secure service integration for accessing customer data and processing payments through virtual accounts, which is a critical requirement in the integration between PT XYZ and its partners. Additionally, this model addresses security challenges related to customer data protection and mitigates the risks of cyberattacks such as data theft, transaction manipulation, and credential misuse. Greybox penetration testing is applied to identify potential vulnerabilities in the API Gateway, token authentication, and inter-system communication. The testing results demonstrate that the integration using this model has low vulnerability and meets established security standards. Its implementation is expected to improve the security, efficiency, and scalability of PT XYZ's digital services.